Penggunaan Ekstrak Buah Kecubung sebagai Bahan Pembunuh Hewan Percobaan Pengganti Chloroform - Aprira Aprira; Lies Winarsih; Helmiyetti Helmiyetti (BIOEDUSAINS:Jurnal Pendidikan Biologi dan Sains, 2022)
This study aims to determine the effectiveness of using ethanol extract of amethyst fruit as an experimental animal killer (euthanasia) substitute for chloroform. The method used is descriptive and experimental methods. The experimental animals used were crickets, cockroaches and frogs. The results showed that the euthanasia test with a volume of 10 ml on experimental cockroach animals after 30 minutes showed that all cockroaches were dead and the LC50 was obtained at a volume of 5.44 ml with intervals of 4.59 to 6.24 ml. In experimental animals, crickets after 20 minutes showed that at 10 ml, almost all crickets died and the LC50 was obtained at a volume of 5.57 ml with intervals of 3.83 to 6.69 ml. As for the experimental frogs, after 20 minutes, all frogs died from the smallest extract volume, which was 2 ml. In conclusion, amethyst fruit extract can be used as an alternative to chloroform for euthanasia of experimental animals in practicum, it's just that the volume of extract used is more than using chloroform. Keywords: Amethyst Fruit, Euthanasia, Cricket, Frog, Cockroach